Dominant prevalence of Porphyromonas gingivalis fimA types I and IV in healthy Japanese children - Yu Shimoyama; Yuko Ohara-Nemoto; Misumi Kimura; Takayuki K. Nemoto; Mitsuro Tanaka; Shigenobu Kimura (Elsevier, 2017)
Background/purpose: Porphyromonas gingivalis is a major causative agent of chronic periodontitis, whilst circumstances for acquisition of the bacterium remain to be elucidated. To examine prevalence of the bacterium harboring distinct fimA types in dental plaque of children, we established PCR procedures that are applicable for specimens with limited amounts. By this method, all six fimA types including type I and Ib were directly identified, and prevalence of fimA types and their frequency of guardian-child transmission in Japanese children were assessed. Materials and methods: Genomic DNA was purified from dental plaque specimens of 132 periodontally healthy children (2-12 years old, 4.8 ± 0.2 years) and 19 mothers of resultant P. gingivalis-positive child subjects. PCR-based fimA genotyping was performed, and untypeable strains in the first PCR analysis were determined by a nested PCR. Results: P. gingivalis was found in 15.2% of the subjects (2-10 years old, 5.1 ± 0.6 years), and the most prevalent types were I and IV (37.0% each), followed by Ib and III (11.1% each), and then II (7.4%). Seven (35.0%) of the 20 P. gingivalis-positive subjects had combined colonization of type I with other fimA types. In most cases, bacterial prevalence and fimA types in the children were distinct from those of their mothers, indicating that its maternal transmission was not significant. Conclusion: These results suggest that colonization of non-disease-associated fimA types I and IV P. gingivalis to the oral cavity initiates from early childhood without showing any periodontal inflammation. Keywords: child, colonization, dental plaque, fimA, genotyping, Porphyromonas gingivalis